Proses Pemilihan Pemimpin Menurut Ibn Taimiyyah - Shobahussurur Amir (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2008)
The echoes of the democratic festival grow louder. The legislative elections on April 9, 2009, as well as the presidential and vice-presidential elections on July 8, 2009, draw nearer. Each promotes the idea that the leader from their party and faction is the most competent and worthy of selection. Leadership in Islam is viewed as a crucial instrument. The absence of leadership would lead to chaos for the nation and state. For this reason, scholars agree that appointing a leader for Muslims is a religious obligation. The following article seeks to explore Ibn Taymiyyah's thoughts on the process of selecting a head of state, the qualifications a leader must possess, and the relationship between the leader and the people.